Amil Zakat Governance Risk Mitigation - Nono Hartono; Achmad Kholiq (Center of Strategic Studies (PUSKAS) BAZNAS, 2021)
Risk in zakat management is a potential event, both predictable and unpredictable, which negatively impacts the level of trust, sharia considerations, and sustainability in the management process. The purpose of this study is to investigate and formulate mitigation efforts of amil zakat governance. The research method uses an Enterprise Risk Management with the Committee of Sponsoring Organizations approach of the Treadway Commission (COSO) modification (ERM-COSO modified) with four indicators discussed that describe the level (likelihood), influence (impact), change (vulnerability) and speed (onset speed). The results of the study indicate that the identified risk of amil governance is as much as nine of the twenty seven risks that should arise with the risk level of amil governance being in an intermediate position. This is different from several previous studies. The level of risk in zakat management is largely determined by the quality of amil. The results of the heatmap analysis resulted in a small dot heatmap size which means a low level of vulnerability to risk (vulnerability), while the dot color consists of six purple, two blue and one red which means the speed of the occurrence of high risk. The impact of this risk identification requires amil recruitment patterns and the provision of good zakat management training. The recommended risk response is to reduce the risk that will occur by (1) implementing reward and punishment for amil to be more professional in carrying out their duties, (2) involving third parties (universities) in monitoring and supervising the distribution of zakat funds.